IMPLEMENTASI METODE TALQIN DALAM PEMBELAJARAN HADIS PADA ANAK USIA DINI DI TK FAKIH AL-KAUTSAR TEMPURREJO WIDODAREN NGAWI - Nurhasanah, Muwahidah (JOURNAL FASCHO : JURNAL PENELITIAN DAN PENDIDIKAN ANAK USIA DINI, 2022)
The Talqin method is a method that has been used to teach the hadith of the prophet by every teacher to his students. This method is the first method in teaching the Qur'an among Muslims. In fact, the teaching of talqin was applied before the teaching of reading and writing. It was the angel Gabriel who mentally recited the Qur'an to the Prophet Muhammad and then he read it back (memorization deposit) to Jibril. Furthermore, the Messenger of Allah (PBUH) mentally recited the Qur'an to his companions, then they deposited their readings and memorization with him. That is what happens in the process of teaching the Qur'an from generation to generation. The Qur'an is learned by students through teachers. The learning of hadith in Fakih Al-Kautsar Kindergarten with the Talqin method is classified into three levels; First, it includes the recitation of hadith from a teacher, imitated by a student, and repeated every day such as hadith about morals, commendable behavior from intentions, ways of eating, speaking, cleanliness, which explains that Islam regulates all problems of human life.